2011
DOI: 10.1016/j.ejphar.2010.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin MC1 receptor in human genetics and model systems

Abstract: The melanocortin MC 1 receptor is a G -protein coupled receptor expressed in melanocytes of the skin and hair and is known for its key role in regulation of human pigmentation. Melanocortin MC 1 receptor activation after ultraviolet radiation exposure results in a switch from the red/yellow pheomelanin to the brown/black eumelanin pigment synthesis within cutaneous melanocytes; this pigment is then transferred to the surrounding keratinocytes of the skin. The increase in melanin maturation and uptake results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 57 publications
0
47
0
Order By: Relevance
“…Population-based studies in diverse ethnic groups have shown the MC1R gene to be highly polymorphic with around 200 allelic variants identified [26,27] , 9 common variants are recognised in populations with European ancestry [28] . In Caucasians, some of the MC1R variants known as R -alleles, with a combined frequency of 18%, have a strong association with red hair, fair skin, freckling as well as increased melanoma and non-melanoma skin cancer risk.…”
Section: Mc1r: α-Msh Receptor and The Gene For Red Hair Colourmentioning
confidence: 99%
See 2 more Smart Citations
“…Population-based studies in diverse ethnic groups have shown the MC1R gene to be highly polymorphic with around 200 allelic variants identified [26,27] , 9 common variants are recognised in populations with European ancestry [28] . In Caucasians, some of the MC1R variants known as R -alleles, with a combined frequency of 18%, have a strong association with red hair, fair skin, freckling as well as increased melanoma and non-melanoma skin cancer risk.…”
Section: Mc1r: α-Msh Receptor and The Gene For Red Hair Colourmentioning
confidence: 99%
“…Conversely, low tyrosinase activity and high availability of cysteine lead to the less photoprotective and potentially phototoxic pheomelanins [31] . The main determinant of the amount and type of pigments formed within epidermal melanocytes is the MC1R genotype status [26,28] .…”
Section: Mc1r: α-Msh Receptor and The Gene For Red Hair Colourmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of low innate levels of eumelanin, fair-skinned individuals are much more prone to acute and chronic effects of UV radiation [16][17][18] . Skin pigmentation, melanoma risk and the ability to "tan" after UV exposure all correlate with the signaling ability of the melanocortin 1 receptor (Mc1r), a G s -coupled seven transmembrane surface receptor on melanocytes [19][20][21][22] . When Mc1r binds its cognate high-affinity ligand, α-melanocyte stimulating hormone (α-MSH), there is activation of adenylyl cyclase and production of the second messenger cAMP 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Of the many developmentally and environmentally induced agonists of MC1R, the hormone αMSH, which is secreted in response to the exposure of keratinocytes to UV radiation, is of particular interest because it mediates the tanning response. Partial or complete loss-of-function mutations in MC1R are the primary cause of a suite of pigmentation traits-red hair, freckles, and unusually light skin that burns but does not tan-that is common in Scotland, Ireland, and, to a lesser degree, other areas of Northern Europe (8). Continental-scale differences in the pattern of variation at MC1R are striking.…”
Section: Local Adaptationmentioning
confidence: 99%